2011
DOI: 10.1007/s10329-011-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

First indications of a highland specialist among mouse lemurs (Microcebus spp.) and evidence for a new mouse lemur species from eastern Madagascar

Abstract: The factors that limit the distribution of the highly diverse lemur fauna of Madagascar are still debated. We visited an understudied region of eastern Madagascar, a lowland rainforest site (Sahafina, 29-230 m a.s.l.) close to the Mantadia National Park, in order to conduct a survey and collect further distributional data on mouse lemurs. We captured, measured, photographed, and sampled mouse lemurs from the Sahafina forest, performed standard phylogenetic methods based on three mitochondrial DNA genes, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…Lemur species numbers have multiplied over the past two decades, largely as a result of taxonomic revisions based on genetic studies (Markolf et al 2011). Mouse lemurs of the genus Microcebus account for much of that increase, with 21 species presently recognized, most of which inhabit very restricted biogeographic ranges and are therefore highly vulnerable to extinction (Andriantompohavana et al 2006; Kappeler et al 2005; Louis et al 2006, 2008; Olivieri et al 2007; Radespiel et al 2008, 2012; Rasoloarison et al 2000, 2013; Yoder et al 2000). The distribution and conservation status of a majority of newly discovered species remain poorly known, however, as there is a lack of studies assessing lemur ecology and population characteristics across disturbance gradients (Irwin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lemur species numbers have multiplied over the past two decades, largely as a result of taxonomic revisions based on genetic studies (Markolf et al 2011). Mouse lemurs of the genus Microcebus account for much of that increase, with 21 species presently recognized, most of which inhabit very restricted biogeographic ranges and are therefore highly vulnerable to extinction (Andriantompohavana et al 2006; Kappeler et al 2005; Louis et al 2006, 2008; Olivieri et al 2007; Radespiel et al 2008, 2012; Rasoloarison et al 2000, 2013; Yoder et al 2000). The distribution and conservation status of a majority of newly discovered species remain poorly known, however, as there is a lack of studies assessing lemur ecology and population characteristics across disturbance gradients (Irwin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…are small, nocturnal primates that inhabit a wide range of habitats throughout Madagascar. As many as 21 species have been described within the genus [21-25], thus a remarkable increase from the two species taxonomy that was recognized as recently as 1994 [26,27]. The geography of the island has historically been considered to play a significant role in explaining divergence patterns among lemurs and other vertebrate species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all segments of the biodiversity of the island are very rich in species, most of them being endemic (Goodman and Beanstead 2003). The rate of discovery of new taxa is unabated, including in supposedly well-known groups such as the lemurs (discovery of a further new species of Microcebus in 2012: Radespiel et al 2012), or the chameleons (a puzzling number of cryptic species has just been demonstrated in the dwarf genus Brookesia: Glaw et al 2012).…”
Section: Introductionmentioning
confidence: 99%